The power of the passive self in English literature, 1640-1770 - Gordon, Scott Paul (Cambridge University Press, 2002)
Challenging recent work contending that seventeenth-century English discourses privilege the notion of a self-enclosed, self-sufficient individual, this study recovers a counter-tradition that imagines selves as more passively prompted than actively choosing. Gordon traces the origins of such ideas of passivity from their roots in the non-conformist religious tradition to their flowering in one of the central texts of eighteenth-century literature, Samuel Richardson's Clarissa